HUBUNGAN DUKUNGAN SUAMI TERHADAP TINGKAT KECEMASAN IBU PADA SAAT PERSALINAN DI KLINIK MITRA ANANDA PALEMBANG - Vera Yuanita; Yuli Suryanti; Adisty Dwi Treasa (Jurnal Kesehatan dan Pembangunan, 2024)
WHO estimates that the Maternal Mortality Rate (MMR) is still very high. Around 287,000 women died during and after pregnancy and childbirth in 2020. In the labor phase there is also an increase in anxiety, with increasing anxiety the intensity of pain will increase. When experiencing anxiety during childbirth, family support is really needed by pregnant women so they can comfort and calm them. The aim of the research was to determine the relationship between husband's support and maternal anxiety levels during childbirth at the Mitra Ananda Clinic in Palembang in 2023. The research method used a cross sectional method. The population in this study were all mothers giving birth at the Mitra Ananda Clinic in Palembang with a sample size of 35 respondents. The research results showed that the distribution of frequency of support from husbands was mostly 20 respondents (57.1%), the mother's anxiety level during childbirth was mostly mild anxiety, 14 respondents (40%). There is a significant relationship between husband's support and the mother's anxiety level during childbirth at the Mitra Ananda Clinic in Palembang in 2023 (p.value = 0.011). Suggestions are expected to further increase the husband's role in the wife's birth by providing counseling to the husband starting when the wife is pregnant to pay more attention to the wife's health condition from the beginning of pregnancy until before delivery.